THE COSMOLOGICAL TEST "MAGNITUDE-REDSHIFT" FOR SOME MODELS OF GRAVITATIONAL END PHYSICAL VACUUM - Aleksandrov, Yu. V.; Bannikova, E. Yu. (Одеські астрономічні публікації, 2017)
The cosmological test m(z) has been calculated condition equation of state p = - ε/3 and p = ε. A case p — ε doesn't contradict observational values of m(z) for quasars.